CHALLENGES AND OPPORTUNITIES FOR THE CHINA INTERNATIONAL COMMERCIAL COURT. Issue 4 (October 2019) - Cai, Wei; Godwin, Andrew
Abstract: China has confirmed its ambition to join the global competition for international business dispute resolution services by establishing the China International Commercial Court (CICC). The CICC has now begun operation following a judicial interpretation issued by the Supreme People's Court. By examining the trial process of the CICC as set out by the Supreme People's Court and comparing the rules with other international commercial courts, this article provides a detailed overview and critical analysis of the issues surrounding cases brought to the CICC. Overall, compared with the approaches adopted by other international commercial courts, the approach adopted by the CICC is conservative. Without bold innovations to China's existing judicial system, the competitiveness of the CICC is likely to be limited. This article argues that it is desirable for the Court to be more actively reformed. Such reforms might also promote judicial reform in China generally and increase China's institutional competitiveness in the global business world. This article also aims to outline the challenges that parties (in particular those from overseas) may face in litigation before the CICC and provide the international community with a critical analysis of the operation and framework of the CICC.